Corrosion Inhibition of Carbon Steel Using Chitosan as an inhibitor in 3.5% NaCl Medium - Lilik Suprianti; Dwi Hery Astuti; Sukamto; Khafid Ubay Ilyas; Ellyn Evina Ellys Simanjuntak (International Journal of Eco-Innovation in Science and Engineering, 2020)
Carbon steel is a metal that is widely used for the construction of industrial and marine applications. Hence, seawater is one of the corrosive mediums due to its Natrium Chloride (NaCl) content as a strong electrolyte. One method to control the corrosion rate is by adding the inhibitor. Chitosan has been chosen as inhibitor corrosion because of non-poisonous and green material. Corrosion inhibition of carbon steel in chitosan inhibitor presence in 3,5% NaCl medium was studied using potentiodynamic polarization technique. This study aims to understand the effect of temperature and inhibitor concentration on carbon steel's corrosion behavior. This study also determined adsorption constant value of chitosan on the carbon steel surface. The corrosion rate has been analyzed by using potentiodynamic polarization. Firstly, carbon steel is prepared by cutting them in cuboid shape by dimensions 4cmx 1cm x 3mm. Secondly, a 3.5 % sodium chloride solution is prepared by dilute NaCl crystal into demineralized water. The next step is inhibitor preparation by dissolve chitosan powder in the acid solution. The corrosion rate is analyzed in different temperatures, various from 30-70oC, and chitosan concentration varied from 0 to 250mg/l. The results showed that chitosan is a promising corrosion inhibitor in sodium chloride medium. The inhibition efficiency at 30oC reaches 84.92% with a chitosan concentration of 250 mg/L.